PENGUJIAN VALIDITAS MODUL INTERAKTIF SIMULASI DAN KOMUNUKASI DIGITAL BERBASIS MACROMEDIA DIRECTOR MX - Rina Sepriana; Rini Sefriani; Indra Wijaya; Pipit Lestari (Universitas Pahlawan Tuanku Tambusai, 2019)
This study aims to determine the level of product validity testing in the form of Interactive Multimedia Learning Media Based on Macromedia Director MX for Class X in SMK-SMAK Padang. This research uses research and development research and development (R&D) methods. Validation is carried out by validators, media experts, material experts and multimedia experts. Evaluation from validator for Learning Media Interactive Multimedia Module Based on Macromedia Director MX in terms of aspects (1) Content worthiness is obtained by an average of 90.4%; (2) the linguistic component is obtained an average of 91.00%; (3) Presentation Components obtained an average of 89.5%; (4) The components of the graphics are 90.3% on average. . Overall validator test assessment of Interactive Multimedia Module Learning Media Based on Macromedia Director MX obtained an overall average of 90.35%, so that the level of validity can be interpreted very validly used so that Learning Media Interactive Multimedia Module Based on Macromedia Director MX for Class X in Padang Vocational High School is interpreted to be very valid in use. Based on the assessment along with expert input and the results of the field testing of learning media Interactive Multimedia Module Based on Macromedia Director MX, it can be concluded that the feasibility has been tested.